Legal feminism and legal pacifism. Critical theories of law and the unconditional repudiation of war - Giolo, Orsetta (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2025)
In this essay, I would like to propose an initial reflection on the significant convergence between legal feminism and legal pacifism in the critique of war. First, I will briefly mention some considerations on legal feminism as a constitutive matrix of critical theories of law; subsequently, I will attempt to analyze the nature of legal pacifism as a critical theory of law. Then, after specifying why legal feminism and legal pacifism should be understood as“unprecedented knowledge”, I will stop, in a schematic way, to analyze their methodological, theoretical and thematic convergence.
Keywords: legal feminism; legal pacifism; critical theory of law; war; violence